2016
DOI: 10.1371/journal.pone.0159023
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic Experiences and Risk of Violence Perpetration and Arrest in the General Population: A Prospective Study

Abstract: BackgroundIn cross-sectional, general population studies, psychotic experiences have been associated with an increased risk of physical violence perpetration and arrest. However, longitudinal research on this topic is lacking. Moreover, it remains unclear whether subjects with psychotic experiences are also at risk of displaying psychological violence. The present study aims to investigate these associations.MethodThe longitudinal association between baseline psychotic experiences and six-year incidence of vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…A study by Keers et al [37] found a strong association between psychotic symptoms and recent aggressive behavior, since 93% of the patients of his sample displayed psychotic symptoms when they committed these offenses, and 47% were “definitely” or “probably” motivated by these symptoms. Other studies have found an association between auditory hallucinations and persecutory delusions and motivation to commit homicide [38–41]. More severe paranoia is associated with greater aggressiveness, even after controlling for factors as impulsiveness, command hallucinations, treatment with antipsychotics, substance abuse, age, and gender [42].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Keers et al [37] found a strong association between psychotic symptoms and recent aggressive behavior, since 93% of the patients of his sample displayed psychotic symptoms when they committed these offenses, and 47% were “definitely” or “probably” motivated by these symptoms. Other studies have found an association between auditory hallucinations and persecutory delusions and motivation to commit homicide [38–41]. More severe paranoia is associated with greater aggressiveness, even after controlling for factors as impulsiveness, command hallucinations, treatment with antipsychotics, substance abuse, age, and gender [42].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual victimisation included unwanted touching, forced undressing and forced sexual activity. Consistent with previous work [ 7 , 36 ], psychological victimisation was defined present if it occurred on two or more occasions, and violent/sexual victimisation on one or more occasions.…”
Section: Methodsmentioning
confidence: 91%
“…One possible explanation is that individuals with PE display disordered behaviour, for example arising from paranoid delusions, leading to social conflict and victimisation. Previous research showed that PE increase the risk of violence perpetration [ 36 ]. Therefore, it is possible that adult victimisation occurs in response to violence perpetration.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Taylor 35 found a strong association between psychotic symptoms and recent aggressive behavior, since 93% of the sample displayed psychotic symptoms when they committed these offenses, and 47% were "definitely" or "probably" motivated by these symptoms. Other studies have found an association between auditory hallucinations and persecutory delusions and motivation to commit homicide [36][37][38][39][40] . More severe paranoia is associated with greater aggressiveness, even when controlling for such factors as impulsiveness, command hallucinations, treatment with antipsychotics, substance abuse, age, and gender 41 .…”
Section: Discussionmentioning
confidence: 99%